1997
DOI: 10.1074/jbc.272.19.12523
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CO Ligation with Nitric-oxide Synthase by Flash Photolysis and Stopped-flow Spectrophotometry

Abstract: Interaction of CO with hemeproteins has physiological importance. This is especially true for nitric-oxide synthases (NOS), heme/flavoenzymes that produce ⅐ NO and citrulline from L-arginine (Arg) and are inhibited by CO in vitro. The kinetics of CO ligation with both neuronal NOS and its heme domain module were determined in the presence and absence of tetrahydrobiopterin and Arg to allow comparison with other hemeproteins. Geminate recombination in the nanosecond time domain is followed by bimolecular associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 44 publications
7
49
2
Order By: Relevance
“…Based on the crystal structures of the oxygenase domain of iNOS (iNOS oxy ), Crane et al (8) concluded that H4B binding resulted in major conformational changes to the protein that are critical for the promotion of subunit assembly into a dimer, the active form of NOS, and the formation of the reductase docking site required for the electron transfer. In addition, biochemical studies of various isoforms of NOS, showed that H4B binding introduces significant changes in protein stability, monomer/dimer equilibrium, proteolytic susceptibility, heme-ligand binding, and substrate binding properties (21)(22)(23)(24)(25)(26). In contrast, based on the crystal structure of the oxygenase domain of eNOS (eNOS oxy ), Raman et al (11) reported that H4B binding does not produce any conformational changes in the protein, and more importantly the dimeric assembly is retained in the absence of H4B.…”
mentioning
confidence: 99%
“…Based on the crystal structures of the oxygenase domain of iNOS (iNOS oxy ), Crane et al (8) concluded that H4B binding resulted in major conformational changes to the protein that are critical for the promotion of subunit assembly into a dimer, the active form of NOS, and the formation of the reductase docking site required for the electron transfer. In addition, biochemical studies of various isoforms of NOS, showed that H4B binding introduces significant changes in protein stability, monomer/dimer equilibrium, proteolytic susceptibility, heme-ligand binding, and substrate binding properties (21)(22)(23)(24)(25)(26). In contrast, based on the crystal structure of the oxygenase domain of eNOS (eNOS oxy ), Raman et al (11) reported that H4B binding does not produce any conformational changes in the protein, and more importantly the dimeric assembly is retained in the absence of H4B.…”
mentioning
confidence: 99%
“…2 shows the fraction of the slow phase in two circumstances for C331A. It also includes, for comparison, data on the WT holoenzyme and data for a heme-binding domain (residues 1-714), both of which were reported previously (14). The fraction of the slow phase is at its maximum when both L-Arg and BH 4 are bound.…”
Section: Resultsmentioning
confidence: 99%
“…As with the WT holoenzyme and heme domain (14), flash photolysis of the CO-ligated C331A mutant displays, in addition to bimolecular association, nanosecond transient absorbance changes that are plausibly attributed to geminate recombination. In all cases, these nanosecond transients are larger whenever the fast phase is larger.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations